PENGARUH PENGGUNAAN WORKSHEET IPA BERORIENTASI HOTS TERHADAP HASIL BELAJAR KOGNITIF SISWA SD MUHAMMADIYAH 4 DAN 5 JAKARTA (Jurnal Pendidikan Dasar, 2019)
This study aims to determine the effect of using Science Worksheet Based-HOTS on cognitive learning outcomes of fifth grade students of SD Muhammadiyah 4 and 5 Jakarta. Design research in this research is Quasi Experimental Design or commonly called a quasi experiment. with the aim that researchers can control all variables that affect the course of the experiment. The independent variable is the use of Science Student’s Worksheet based-HOTS and the dependent variabel is students' cognitive learning outcomes. The research subjects were 62 students, consisting of 34 students for the experimental class, and 28 control class students. The research instrument used to collect data is a test of students' Cognitive Science learning outcomes. Data from the pretest and posttest results were analyzed using independent t-test with a significance level of 5% (α = 0.05). Based on the data from the t-test analysis results obtained for pretest values, t-count ≥ t-table is 1,810 35 2,035 so it can be concluded that there is no significant difference between the control class and the experimental class. Whereas for the posttest value, the value of t-table is 10,053 ≥ 2,035, it can be concluded that there are significant differences between the results of the post-test control class and the experimental class. This shows that there is a significant effect of the application of Science Worksheet Based-HOTS to Student’s science cognitive learning outcomes of elementary school students of Class V Muhammadiyah 4 and 5 Jakarta